Perlindungan Data Pribadi Dalam Era Big Data : Implikasi Hukum Di Indonesia - Putra, Rengga Kusuma; Idris, Maulana Fahmi; Widhiati, Greget (Universitas Sains dan Teknologi Komputer, 2024)
This study examines the challenges and effectiveness of the Personal Data Protection Law (UU PDP) in Indonesia amidst the rapid expansion of Big Data. As digital data collection and processing become increasingly integral across sectors, this study identifies gaps in policy implementation, particularly among small and medium enterprises (SMEs), which often lack resources for comprehensive data protection. Through interviews and document analysis, findings indicate that while the UU PDP establishes a necessary legal framework, its implementation faces obstacles, including limited adoption of encryption and anonymization technologies and low public awareness of data privacy risks. These challenges highlight the need for enhanced governmental support, technical guidelines, and public education to improve data security practices. This study contributes to ongoing policy discussions by offering practical recommendations to strengthen data protection in Indonesia and foster a safer digital environment for individuals.